2022
DOI: 10.3390/antiox11030452
|View full text |Cite
|
Sign up to set email alerts
|

Algal Metabolites Can Be an Immune Booster against COVID-19 Pandemic

Abstract: The world has faced the challenges of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) for the last two years, first diagnosed at the end of 2019 in Wuhan and widely distributed worldwide. As a result, the WHO has proclaimed the illness brought on by this virus to be a global pandemic. To combat COVID-19, researcher communities continuously develop and implement rapid diagnoses, safe and effective vaccinations and other alternative therapeutic procedures. However, synthetic drug-related side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 154 publications
0
11
0
Order By: Relevance
“…Furthermore, fucoidan extracted from Adenocystis utricularis , Cystoseira indica , Fucus vesiculosus , and Undaria pinnatifida exhibited anti-inflammatory activity by inhibiting adhesion and blocking reverse transcriptase enzyme (Kuznetsova et al 2020 ; Krylova et al 2020 ). Similarly, galactans are the main polysaccharide found in different marine seaweeds (Kumar et al 2022a , b ). Galactans extracted from Agardhiella tenera , Schizymenia binderi , and Callophyllis variegate exhibited antiviral activity by blocking the viral adhesion and replication into host cells (Ohta et al 2009 ).…”
Section: Marine-derived Bioactive Compounds For the Treatment Of Covi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fucoidan extracted from Adenocystis utricularis , Cystoseira indica , Fucus vesiculosus , and Undaria pinnatifida exhibited anti-inflammatory activity by inhibiting adhesion and blocking reverse transcriptase enzyme (Kuznetsova et al 2020 ; Krylova et al 2020 ). Similarly, galactans are the main polysaccharide found in different marine seaweeds (Kumar et al 2022a , b ). Galactans extracted from Agardhiella tenera , Schizymenia binderi , and Callophyllis variegate exhibited antiviral activity by blocking the viral adhesion and replication into host cells (Ohta et al 2009 ).…”
Section: Marine-derived Bioactive Compounds For the Treatment Of Covi...mentioning
confidence: 99%
“…Furthermore, sulfolipids and glycolipids present in marine seaweeds are reported to exhibit antiviral activities against the SARS-CoV-2 infection (Kumar et al 2022a , b ).…”
Section: Marine-derived Bioactive Compounds For the Treatment Of Covi...mentioning
confidence: 99%
“…The disease was first diagnosed at the end of 2019 in Wuhan and later on WHO proclaimed that the illness brought on by this virus was a global pandemic. Researchers incessantly tried to develop and implement rapid diagnoses, safe and effective vaccinations and other alternative therapeutic procedures to combat this deadly disease (Lai et al 2020 ; Kumar et al 2022 ). However, synthetic drug caused side effects and high costs to benefit ratio changed researcher’s interests in natural product-based medicines.…”
Section: Antiviral Applications Of Algae Metabolitesmentioning
confidence: 99%
“…Therefore, antiviral substances derived from natural resources and some medicines have seen a boom in popularity recently. Algal-derived metabolites can be also used as antibodies and vaccine raw materials against COVID-19 (Kumar et al 2022 ). Recent studies have reported that these compounds demonstrate substantial activity against a wide array of DNA and RNA viruses, including the influenza virus known to be associated with respiratory illnesses (Ben Hlima et al 2022 ).…”
Section: Antiviral Applications Of Algae Metabolitesmentioning
confidence: 99%
“…Microalgal extracts are ideal sources of biotechnological compounds with high levels of bioactivity, e.g., potent antiviral, anti-microbial, anti-oxidant, anti-inflammatory, anti-cancer, and immune-enhancing properties; neuroprotective activity; and various therapeutic and restorative properties. Furthermore, compounds or metabolites derived from microalgae can be used as antibodies and raw materials for vaccine production against SARS-CoV-2 [2,3].…”
Section: Introductionmentioning
confidence: 99%